1981
DOI: 10.1021/np50013a003
|View full text |Cite
|
Sign up to set email alerts
|

The Alkaloid Patterns of Cell Suspension Cultures and Differentiated Plants of Baptisia Australis and Their Biogenetic Implications

Abstract: ABsm.icT.-Alkaloid extracts from Biifilisifi fiztstrtilis leaves, analyzed by capillary gas chromatography and gc/ms, were shown to contain sparteine ( l ) , lupanine (6), cytisine (3), A'-methylcytisine (2), anagyrine (U), 17-ososparteine (ll), 13-hydroxyanagyrine (lo), Fi,C~dehydrolupanine (4), tinctorine (7) (new for Bnplzsiti), isot inctorine ( 5 ) (new alkaloid) and 13-acetoxyanagyrine (9) (new alkaloid).The alkaloid content of cell suspension criltures was three orders lower than that (Jf the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…Oven program temperature was 150-280C, increasing at a rate of 2C/min and held at 280C for 15 min. The injector and the auxiliar detector temperature were 250C and 280C, respectively (Verdoorn and Wyk 1991;Wink et al 1981).…”
Section: Stems Leaves and Podsmentioning
confidence: 99%
“…Oven program temperature was 150-280C, increasing at a rate of 2C/min and held at 280C for 15 min. The injector and the auxiliar detector temperature were 250C and 280C, respectively (Verdoorn and Wyk 1991;Wink et al 1981).…”
Section: Stems Leaves and Podsmentioning
confidence: 99%
“…All alkaloids mentioned in this study have been previously identified by capillary glc/m ass spec trometry (AEI MS 30, D ata System DS 50) [8,[14][15][16], The alkaloid signals in the different glc-runs were identified using reference alkaloids and their specific retention indexes.…”
Section: Capillary Gas-liquid Chromatographymentioning
confidence: 99%
“…Some authors postulated sparteine to be a key intermediate in the formation of the tetracyclic alkaloids [5][6][7]. To the contrary, more recent research indicates that this compound may also be derived via 17-oxosparteine or lupanine [1,3,8].…”
Section: Introductionmentioning
confidence: 99%